Screening for F508del as a first step in the molecular diagnosis of cystic fibrosis, - Marson, Fernando Augusto de Lima (Sociedade Brasileira de Pneumologia e Tisiologia, 2013)

(untitled)
OBJECTIVE: To determine the relevance of screening for the F508del mutation of the cystic fibrosis transmembrane conductance regulator gene as a first step in the genetic diagnosis of cystic fibrosis (CF) by associating the genotype with various clinical variables. METHODS: We evaluated 180 CF patients regarding the F508del mutation. The clinical data were obtained from the medical records of the patients and from interviews with their parents or legal guardians. RESULTS: Of the 180 patients studied, 65 (36.1%) did not carry the F508del mutation (group 0 [G0]), 67 (37.2%) were F508del heterozygous (G1), and 48 (26.7%) were F508del homozygous (G2). All three groups showed associations with the clinical variables. Homozygosis was associated with younger patients, younger age at CF diagnosis, and younger age at the first isolation of Pseudomonas aeruginosa (PA), as well as with higher prevalence of pancreatic insufficiency (PI) and non-mucoid PA (NMPA) colonization. In comparison with G1+G2 patients, G0 patients were older; first experienced clinical symptoms, digestive disease, and pulmonary disease at an older age; were older at CF diagnosis and at first PA isolation; and had a lower prevalence of PI and meconium ileus, as well as of colonization by NMPA, mucoid PA, and Burkholderia cepacia. In G1 patients, values were intermediate for age at CF diagnosis; age at first PA isolation, first pulmonary symptoms, and first clinical manifestations; MPA colonization; and OR for PI. CONCLUSIONS: The identification of F508del in 63.9% of the patients studied showed that this can be a useful tool as a first step in the genetic diagnosis of CF. The F508del genotype was associated with clinical severity of the disease, especially with the variables related to CF onset.